Überblick über wichtige zivil- und zivilverfahrensrechtliche Entscheidungen des japanischen Obersten Gerichtshofs aus dem Jahre 2008 - Tidten, Dan (Zeitschrift für Japanisches Recht, 2011)
The author gives an overview of important civil law decisions of the Supreme Court in 2008, dealing with the property law, law of obligations, commercial law, law of procedure, and private international law.